An investigation on the use of GNSS-IR method for determining sea level changes and its accuracy analysis - Altuntas, Cemali; Tunalioglu, Nursu (Geomatik Journal, 2022)
GNSS Interferometric Reflectometry (GNSS-IR) allows retrieving environmental characteristics around the GNSS antenna by analyzing the GNSS data. When the GNSS antenna located at the seashore has sufficient open view for receiving reflections from the sea surface, sea level changes can be determined based on the GNSS-IR method. In this study, the determinability of the sea level changes based on GNSS-IR was analyzed with 1-year static GPS data dated 2020 using SNR1 and SNR2 (L1 and L2 frequencies) values of Tekirdag station (TEKR), which is involved to CORS-TR Network. In the analyses, frequency limit, satellite elevation angle limit, background noise condition (BNC) obtained by spectral analysis and median absolute deviation (MAD) condition were considered. In order to evaluate the accuracy of the estimation results, 18 different analysis strategies were created, and sea level measurements provided by the TUDES Marmara Ereglisi tide gauge were used as verification data. The results were also examined in terms of the number of estimates (NE) obtained from the data and the number of daily estimates coverage in 1-year data. Accordingly, the highest correlation for 1-year data was found to be 75% (NE: 1911, Coverage: 279) for SNR1 with 5 degrees-20 degrees elevation angle and 5BNC condition. When monthly evaluations were made with the strategy in which the highest correlation was obtained for the annual data, correlation values of up to 84% for SNR1 and 88% for SNR2 were obtained.
Keywords: GNSS-Interferometric; Reflectometry (GNSS-IR); Sea Level; Lomb-Scargle Periodogram (LSP); Signal-to-Noise Ratio (SNR); SOIL-MOISTURE; GPS MULTIPATH; SNR DATA; REFLECTOMETRY; GLONASS; TIDES; Geology; Remote Sensing